Impact of transalpine rail network disruptions: A study of the Brenner Pass. (June 2016) - Fikar, Christian; Hirsch, Patrick; Posset, Martin; Gronalt, Manfred
Abstract: This work investigates the impact of sudden rail closures on transportation networks and the local industries affected. A decision support system is introduced, which automatically generates a rail network and simulates passenger and freight traffic. In case of rail closures, freight traffic is rerouted and resulting delays are calculated. Furthermore, the option to transship from rail to road at terminals is enabled. The model is tested using data originating from a major transalpine rail corridor, the 'Brenner Pass', which connects Austria and Italy. Results show rail links which are critical and the impact of various disaster scenarios is compared. Highlights: This work studies the impact of transalpine rail network disruptions. Rail networks and traffic are simulated to calculate resulting delays. The option to transship between rail and road at terminals is given. The model is tested on sudden closures of the 'Brenner Pass'. Experiments show criticality of links and compare various disruption scenarios.